A high burden of cytomegalovirus marks poor vascular health in transplant recipients more clearly than in the general population. Issue 2 (11th February 2019) - Lee, Silvia; Brook, Emily; Affandi, Jacquita; Howson, Prue; Tanudjaja, Selita Agnes; Dhaliwal, Satvinder; Irish, Ashley; Price, Patricia
Abstract: Objectives: Meta‐analyses have now confirmed that persistent infections with cytomegalovirus (CMV) can accelerate the onset of diseases of ageing, notably cardiovascular pathologies. We address the circumstances in which the association may be strong enough to warrant intervention to reduce the viral burden. Results: We compare markers of the burden of CMV with established indices of vascular pathology in healthy adults ( n = 82) and in renal transplant recipients (RTR; n = 81). Levels of all inflammatory and vascular biomarkers and CMV antibodies were higher in RTR, and flow‐mediated dilation (FMD) values were lower indicating inferior endothelial function. In multivariable regression models without adjustment for estimated glomerular filtration rate (eGFR), CMV antibody levels, age and gender were independently associated with FMD in RTR, whilst only CRP associated with FMD in healthy adults. After adjustment for eGFR, associations between CMV antibody and FMD in RTR were reduced. Methods: Carotid intima‐media thickness, FMD, eGFR and plasma levels of CMV antibodies (reactive with a lysate, CMV IE‐1 or CMV gB), ICAM‐1, VCAM‐1, P‐selectin, sIFNαR2, sTNFR1, sCD14 and CRP were determined. Conclusion: Levels of CMV antibody predict declining endothelial health in RTR and not in healthy adults, presumably by reflecting a high burden of CMV. The levels of CMV antibodies were a poor reflection of plasma biomarkers thought to reflect 'inflammaging' or vascular damage. Abstract : Cytomegalovirus (CMV) has been linked with many diseases of ageing, notably vascular pathologies, but we lack appropriate criteria to determine who should receive antiviral therapy. Here, we show that transplant recipients retain a higher burden of CMV, elevated markers of immune activation and vascular pathology over many years. We link their high CMV antibody levels with reduced flow‐mediated dilation of the brachial artery and show that CMV antibody predicts a poor FMD more effectively than standard biometrics or biomarkers.